EMBEDDING GRADUATE ATTRIBUTES INTO THE FOUNDATION PROGRAMME: REFLECTIONS ON PROCESS AND PRODUCT - Mashiyi, Nomakhaya (South African Journal of Higher Education, 2016)
In this paper, the author explores how a Bachelor of Commerce Extended Curriculum Programme (ECP) lecturer embedded the desired University of the Western Cape UWC graduate attributes into the curriculum and describes his experience of the curriculum alignment process. Using document analysis, the researcher in the case study examined the Analytical and Critical Thinking-Foundation (ACF) module outline to determine how the UWC graduate attributes were constructively aligned with learning outcomes, teaching-learning activities, assessment criteria and assessment methods. A focused interview was conducted with the lecturer to determine how he had experienced the curriculum alignment exercise. The case study revealed that constructive alignment is central to good teaching and that ECPs are as important as regular programmes for embedding graduate attributes as they provide a context for lecturers to align the curriculum, adjust their teaching and assessment practices and reflect on their classroom practices.